Optically-powered Hybrid RoF/VLC Systems for 6G Applications - Pinto, Felipe Batista (2024)
This dissertation presents the implementation of two power-over-fiber (PoF) systems, aiming to optically feed two different architectures of 5G/6G networks. The first implementation is regarding the deployment of a radio-over-fiber (RoF)-based 5G New Radio (NR) system in conjunction with PoF for industrial environments. A 100 MHz bandwidth 5G NR signal centered at 3.5-GHz is transmitted throughout a 20-km single-mode optical fiber (SMF) link. Regarding the PoF system, a 5-W optical power is transmitted through a 100-m conventional multimode optical fiber (MMF) link with 62.5 ??m core diameter, with the purpose of powering an RoF module. It achieves a PoF system power transmission efficiency (PTE) of around 19% and the 5G NR system performance is evaluated as a function of the root mean square er ror vector magnitude (EVMRMS). A throughput of 600 Mbps is achieved with no performance degradation when compared to a conventional electrically-powered RoF system, demonstrating the applicability and potential of the PoF technique for 5G NR-based industrial communications. The second implementation relies on a hybrid optically-powered visible light communication (VLC) and fiber-wireless (FiWi) sys tems towards 6G indoor applications. The proposed PoF system is able to energize two loads, a RoF module, which contains a photodetector and an RF amplifier, and a VLC red laser. A 500 m conventional MMF link is used to transport 8.1 W optical power, obtaining approximately 1.06 W electrical power and a PTE of 14%. Regarding the communication link, a 5G NR signal is transmitted throughout a 10-km SMF fronthaul based on RoF technology, before being radiated in a hybrid access networks based on RF and VLC links. It is demonstrated a 1.2 Gbps throughput in the VLC link using a 5G NR signal with 200-MHz bandwidth and 64 quadrature amplitude modulation (QAM), resulting in approximately 4.02% EVMRMS. Finally, another comparison be ween the PoF system and a conventional power supply is performed, validating the PoF system applicability for the 5G/6G indoor networks.